2016
DOI: 10.1101/049163
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mega-analysis of 31,396 individuals from 6 countries uncovers strong gene-environment interaction for human fertility

Abstract: Authors SummaryFertility behavior -such as age at first birth and number of children -varies strongly across historical time and geographical space. Yet, family and twin studies, which suggest that up to 50% of individual differences in fertility are heritable, implicitly assume that the genes important for fertility are the same across both time and space. Using molecular genetic data (SNPs) from over 30,000 unrelated individuals from six different countries, we show that different genes influence fertility i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Of note, consistent heritability estimates across different levels of the stratifying variable do not completely eliminate the potential existence of GxE interactions. Specifically, recent studies have identified genetic heterogeneity in human traits such as BMI and fertility [62,63], indicating that the genetic architecture of a trait may be different across environments (i.e., the genetic correlation of a trait in different environments may be significantly smaller than 1) even if the overall heritability estimates are similar. Dissection of common and unique environmental influences and their interactive effects with genetics on different complex traits, and the shared and unique genetic effects across environments are important future directions to explore.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, consistent heritability estimates across different levels of the stratifying variable do not completely eliminate the potential existence of GxE interactions. Specifically, recent studies have identified genetic heterogeneity in human traits such as BMI and fertility [62,63], indicating that the genetic architecture of a trait may be different across environments (i.e., the genetic correlation of a trait in different environments may be significantly smaller than 1) even if the overall heritability estimates are similar. Dissection of common and unique environmental influences and their interactive effects with genetics on different complex traits, and the shared and unique genetic effects across environments are important future directions to explore.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we explored whether different genetic markers influence Neuroticism in different environments by testing for Gene × Environment interactions in a combined data set, using the cohort of origin as a proxy for the different environments (cf. Tropf et al, ).…”
Section: The Biological and Genetic Basis Of Neuroticismmentioning
confidence: 99%
“…Specifically, the G allele of rs2523393 was associated with longer intervals to pregnancy and lower expression of the HLA-F in mid-secretory phase (receptive) endometrium, whereas the A allele was associated with shorter intervals to pregnancy and higher HLA-F expression. The median time to pregnancy, for example, was 2.3, 2.6, and 4.9 months among women with the AA, GA, and GG genotypes, respectively [1][2][3]6 .…”
Section: Introductionmentioning
confidence: 99%
“…Female reproductive traits such as fertility, fecundity, and fecundability are heritable in humans 1,2 , however, identifying the genetic bases for these traits has been challenging [1][2][3] . We previously performed an integrated expression quantitative trait locus (eQTL) mapping and association study to identify eQTLs in mid-secretory endometrium that influence pregnancy outcomes 1,2,[4][5][6] .…”
Section: Introductionmentioning
confidence: 99%